Islam and Democracy: A Comparative Study Between the Islamic System of Governance and Modern Democracy: Islam dan Demokrasi: Studi Komparatif antara Sistem Pemerintahan Islam dan Demokrasi Modern - Srimulyani, Ema; Nurhanisyah, Siti; Najmul Umam Assondani, Muhammad Mufti (JSPH : Jurnal Sosial Politik Humaniora, 2024)
This study examines a comparison between the Islamic governance system and modern democracy, highlighting their fundamental principles, governance structures, and implementation in state affairs. The Islamic governance system is based on the Qur'an and Sunnah, emphasizing justice, consultation (shura), and trustworthy leadership, while modern democracy is founded on popular sovereignty, individual freedom, and the rule of law. A key difference lies in the source of power legitimacy: in Islam, legitimacy stems from divine revelation and Sharia law, whereas in modern democracy, it derives from the people's will, expressed through electoral mechanisms. Nevertheless, both systems share commonalities, such as prioritizing public participation and striving for social justice. This study also explores how these systems are applied in various countries, encompassing both theocratic governments and secular democracies. The findings reveal that Islamic values can be integrated into the framework of modern democracy to establish more inclusive, ethical, and contextually relevant governance. This research aims to provide valuable insights into the relationship between Islam and democracy while inspiring the developmentof governance systems that are more just and aligned with contemporary global challenges.